2002
DOI: 10.1002/jbm.1280
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of fluorinated polyimide

Abstract: Contact between blood and biomaterial triggers a complex series of events including protein adsorption, leukocyte adhesion and activation, and complement activation. In this article, a series of fluorinated polyimides cured at a different temperatures was prepared, and the biocompatibility of the membranes was evaluated using in vitro protein adsorption, neutrophil adhesion, and complement activation experiments under static conditions. We found that protein adsorption, neutrophil adhesion, and complement acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…1. The results of this qualitative analysis, which demonstrated that the microelectrode and control surfaces were not toxic to the human and mammal cells (Black, 1999), along with the widely accepted use of polymides and gold in biomedical devices (Schneider and Steiglitz, 2004;Liu et al, 2003;Kanno et al, 2002;Klinge et al, 2001), suggest that the Kapton and gold microelectrode array is suitable for use with human patients.…”
Section: Methodsmentioning
confidence: 96%
“…1. The results of this qualitative analysis, which demonstrated that the microelectrode and control surfaces were not toxic to the human and mammal cells (Black, 1999), along with the widely accepted use of polymides and gold in biomedical devices (Schneider and Steiglitz, 2004;Liu et al, 2003;Kanno et al, 2002;Klinge et al, 2001), suggest that the Kapton and gold microelectrode array is suitable for use with human patients.…”
Section: Methodsmentioning
confidence: 96%
“…12 A carbon pigment makes the inlay opaque. Sixteen hundred holes (25 mm diameter) arranged in a randomized pattern allow nutritional flow through the implant into the anterior stromal tissue to prevent corneal melting.…”
Section: Corneal Inlaymentioning
confidence: 99%
“…By Förster theory, 22 the efficiency of energy transfer (E) is related to the distance R (Å) between the donor and acceptor by 6 6…”
Section: Binding Parametersmentioning
confidence: 99%
“…4,5 In recent publications, more studies have been focused on the study on biocompatibility of polyimide. 6,7 In this paper, we report the interaction between a kind of heteroaromatic diamine monomer (2,6-bis[4-(4-amino-2-trifluoromethyl phenoxy)benzoyl] pyridine (BAFP, the chemical structure shown in Figure 1 8 ) with human immunoglobulin (HIgG) under simulated physiological conditions by molecular modeling and different spectroscopic methods. The partial binding parameters of the reaction were calculated through SGI FUEL workstations.…”
Section: Introductionmentioning
confidence: 99%